Researchs of genicode and war crimes criminal cases of Special investigation department of General procecutor office. - Sabutis, Liudvikas (Genocidas ir rezistencija, 2002)
The main function of the investigation and control of genocide, as well as war crimes in Lithuania, is performed by the Special Investigation Division of the Prosecutor General’s Office. The Special Investigation Division organises and makes investigations into crimes of genocide of the Lithuanian population and crimes against humanity, controls such investigation, examines and summarises the practice of investigating facts of genocide of the Lithuanian population, provides methodological assistance to local and regional prosecutor’s offices, acts as an intermediary for foreign counterparts in finding evidence in Lithuanian archives, and assists in the identification and interviewing of potential witnesses.
Keywords: genocide; war crimes; law; law inforsement institution